Perbankan Syariah dan Pertumbuhan Ekonomi Indonesia: Bagaimana Kontribusinya? - Emy Widyastuti; Yusvita Nena Arinta (AL-MUZARA'AH, 2020)
Islamic banking takes part in the Indonesian economic and financial system which contributes to the dynamics of eeconomic growth. The number of Islamic banks in Indonesia, through its market share, is still quite small, namely 5.95% in 2019 of the total national banking market share. One of the main activities of Islamic banking is channeling financing through financing based on the type of use and business category. This study aims to determine the short-term and long-term contribution of Islamic banking to Indonesia's economic growth using the Vector Error Correction Model (VECM) method. The data used in this study are quarterly secondary data of real Gross Domestic Product (GDP) and financing based on the use and category of Indonesian Islamic banking business types, which consist of working capital financing, investment financing and consumption financing. The results showed that in the short and long term, the variable consumption financing had a significant negative effect on Indonesia's economic growth.